Multimedia mobile learning application for childrenâs education: The development of MFolktales - Ibrahim, N. (Canadian Center of Science and Education, 2015)
Children learn from what they see and hear. One of the attractive applications is animation story and these children are exposed to various types of animation story. However, not all animation stories presented are suitable for childrenâs education in terms of exaggeration elements applied in animation. Furthermore, the existence of mobile application does not emphasize the touch gesture that is suitable for childrenâs age. Hence, there is a lack of mobile learning applications with education-oriented environment for childrenâs education. Therefore, there is a need for research to develop a well-designed mobile application with suitable exaggeration elements together with good story plots and socio-cultural values to educate as well entertain children. This paper discusses the design and development of Malay folktales mobile application called MFolktales based on a local Malay folktale story. MFolktales is an Android-based application and it was developed based on the validated conceptual model as well as analyzed and defined design principles and requirements. This paper presents the development process of MFolktales application. The development life cycle was adopted from ADDIE Instructional Design (ID) model, taking into consideration the animation development process of pre-production, production, and post-production. Overall, there are five phases involved in the development life cycle: analysis, design, development, implementation and evaluation. The application was tested to strengthen its functionality and usability. The result shows that MFolktales application is ready to be tested to real users and ready to be commercialized. Â© 2015, Canadian Center of Science and Education. All rights reserved.